Dynamic molecular size transformation of aquatic colloidal organic matter as a function of pH and cations. (1st November 2018) - Xu, Huacheng; Lin, Hui; Jiang, Helong; Guo, Laodong
Abstract: Knowledge of the dynamic changes in molecular size of natural colloidal organic matter (COM) along the aquatic continuum is of vital importance for a better understanding of the environmental fate and ecological role of dissolved organic matter and associated contaminants in aquatic systems. We report here the pH- and cation-dependent size variations of COMs with different sources (river and lake) quantified using flow field-flow fractionation (FIFFF), fluorescence spectroscopy and parallel factor analysis (PARAFAC), attenuated total reflectance Fourier transform infrared (ATR–FTIR) spectroscopy, and zeta potential analysis. Increasing pH caused a decline in molecular sizes and an obvious size transformation from the >10 kDa to 5–10 kDa and further to 1–5 kDa size fraction, whereas the opposite trend was observed for increasing cation (e.g., Ca 2+ and Cu 2+ ) abundance. Compared with lakewater COM, the riverwater COM exhibited a greater pH-dependent dispersion but less extent in cation-induced aggregation, demonstrating that the dispersion and aggregation dynamics were highly dependent on COM source and solution chemistry (e.g., pH and cations). Based on ATR–FTIR analysis, the extensive dissolution of C=O and C–O functional groups resulted in a greater pH-dependent dispersion for river COM. Fluorescence titration revealed that, despite their similar cation-induced aggregation behavior, the binding constants of all the PARAFAC-derived components for Cu 2+ were 1–2 orders of magnitude higher than those for Ca 2+ ( logK M : 4.54–5.45 vs. 3.35–3.70), indicating a heterogeneous nature in cation-DOM interactions. The greater extent of decline in zeta potential for lake COM suggested a Ca-induced charge neutralization and aggregation mechanism. However, for Cu-induced aggregation, chemical complexation was the predominant pathway for the river COM, with higher binding constants, while charge neutralization and chemical complexation co-induced the aggregation of lake COM. Thus, natural COMs may have different environmental behavior along the aquatic continuum and further affect the fate and transport of contaminants in aquatic environments. Graphical abstract: Highlights: Increased pH causes COM to disperse from larger (>10 and 5–10 kDa) to smaller (1–5 kDa) sized NOM. Increased cation enhances COM coagulation/aggregation to form larger sized COM. River COM exhibited greater pH-dependent dispersion but less cation-induced aggregation than lake COM. Extensive dissolution of C=O and C–O groups accounted for a greater pH-induced dispersion for river COM. Compared to river COM, charge neutralization and chemical complexation co-induced the aggregation of lake COM.